An appraisal of Majallat al-Ahkam al-Adliyyah: a legal code of Islamic civil transactions by the Ottoman - Rahman, Habibur; Osmani, Noor Mohammad (Human Resource Management Academic Research Society, 2018)
The Majallat al-Ahkam al-Adliyyah, known as the Mejelle, is a legal code of Islamic civil transactions drafted under the auspices of the Ottoman. This study intends to introduce the Mejelle and to evaluate the codification attempt made by the Mejelle. Employing analytical and critical methods the study finds out that in codification of Islamic civil transactions the attempt of the Mejelle is comparatively more successful and it explicitly distinguishes between the method of being reference for learning and reference for judiciary. The study demonstrates that generally the Mejelle consents to the preponderant views of Hanafi School, excluding few cases in which it conforms to minority Hanafi views considering public wellbeing and needs of the time. Nevertheless, the compilation process of the Mejelle complies with the principles of giving preponderance of the Hanafi School of Islamic law.